PSYCHOLOGICAL EXAMINATION IN CRIMINAL CASES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the role of forensic psychological examination (FPE) as an important tool in criminal proceedings. It examines the historical aspects of FPE development, its current state, and future prospects. Special attention is given to the tasks addressed by FPE, such as determining the sanity of the accused, assessing psychological influence on the victim, detecting signs of deception in testimony, and others. The article also explores legal and methodological issues related to the appointment and conduct of FPE and suggests ways to improve its effectiveness in criminal proceedings and protect the rights of participants.